Profil fitokimia dan aktivitas antibakteri fraksi etil asetat daun jarak pagar (Jatropha curcas) - Sudarman Rahman (Pandawa Institute, 2022)
Bacterial infection is a major cause of chronic infection and death that continues to threath public health worldwide. Improper use of antibiotics can cause pathogenic bacteria to become resistant to antibiotics and have side effects, so alternative sources of antibiotics from natural ingredients are needed. One type of plant that is efficacious as an antibacterial is jarak pagar leaves (Jatropha curcas). This study aims to examine the phytochemical content qualitatively using the tube method and the antibacterial activity of the ethyl acetate fraction of jarak pagar leaves using the disc diffusion method. Extraction of jarak pagar leaves by maceration method with 96% ethanol then fractionated with ethyl acetate. Data on the diameter of the inhibition zone in the antibacterial test were analyzed using the non-parametric test, namely the Kruskal Wallis test. The analysis was continued with Mann Whitney's post hoc with a confidence level (pvalue<0.05). Based on the results of the phytochemical test obtained alkaloids, saponins, flavonoids, polyphenols and tannins. The antibacterial activity of the ethyl acetate fraction of jarak pagar leaves at a concentration of 8 mg/mL showed an inhibition zone of 19.73±0.25 mm which was included in the very moderate category and weakly inhibited at a concentration of 0.5 mg/mL which was 4.87±0.31 mm and the results of statistical tests showed that the ethyl acetate fraction of jarak pagar leaves had antibacterial activity and each concentration had a significant effect on inhibiting the growth of S. aureus.